DEMOGRAPHIC DETERMINANTS OF ORGANISATIONAL COMMITMENT: THE NIGERIAN EXPERIENCE (Academicia Globe: Inderscience Research, 2023)
In this investigation, the correlation between employees’ demographic traits and their commitment to the organization was explored. A sample of 265 employees was randomly selected from fifteen deposit money Banks in the Niger Delta Region of Nigeria. Employing a quasi-experimental research design deemed most suitable for administrative sciences, data were gathered through a cross-sectional survey, specifically utilizing a questionnaire. Data analysis involved employing the Spearman Rank Correlation Coefficient and the Multiple Regression Model using the Statistical Package for Social Sciences (SPSS) version 15. The results demonstrated a strong positive and statistically significant association between demographic characteristics and organizational commitment within deposit money banks. Particularly, age, educational attainment, and tenure in the job exhibited a robust positive and statistically significant correlation with measures of organizational commitment (affective, normative, and continuance). Likewise, male employees displayed greater commitment to the organization compared to their female counterparts, while married employees exhibited higher commitment levels than their single counterparts. From these findings, it is concluded that age, educational level, and job tenure significantly contribute to enhancing affective, normative, and continuance commitments among employees in the Nigerian banking sector. Furthermore, the study suggests that male employees tend to show more commitment to the organization than females, and married employees demonstrate higher commitment levels than singles. Theoretical and managerial implications derived from these findings for effectively managing organizational commitment in the workplace are discussed.